Documentary evidence for changing climatic and anthropogenic influences on the Bermejo Wetland in Mendoza, Argentina, during the 16th 20th century - Prieto, Maria del Rosario (2012)
This paper examines the processes underlying changes to the once-extensive Bermejo Wetland, east of the city of Mendoza, Argentina (32550 S, 68510 W). Historical documents and maps from the 16th to 20th century are used to reconstruct environmental shifts. Historical documents indicate periods of increased snowfall in the adjacent Andes mountains, as well as high flow volumes in the Mendoza River. Data from georeferenced maps, the first from 1802 and the last from 1903, reflect the changes in the surface area of the wetland. The combined data sets show pulses of growth and retraction, in which major expansions coincided with more intense snowstorms and increased flow in the Mendoza River, which in turn influenced socio-economic activities. The wetland became progressively drier during the 19th century, before drying up completely around 1930, due in part to the construction of drainages and channels.